Developing reflective and investigative skills in teacher preparation programs: the design and implementation of the classroom research component at the foreign language program of Universidad del Valle - Cárdenas Ramos, Rosalba; Faustino, Carmen Cecilia (Colombian Applied Linguistics Journal, 2003)
In this article we want to describe our process and experience in studying, designing, planning and implementing the Classroom Research Component in the first five semesters of the Licenciatura program at the School of Language Science, Universidad del Valle. We want to stress the role of Classroom Research in our students’ initial training and in our own professional development. We also want to show the importance of preparing students and future teachers who possess not only linguistic competence in the foreign languages, but also competences that allow them to reflect, analyze and find ways of improving their professional practice. The description of this experience leads us to share our achievements, difficulties and plans for future development.